2020
DOI: 10.1073/pnas.1915313117
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of extensive fine-scale diversity by ecologically driven spatiotemporal chaos

Abstract: It has recently become apparent that the diversity of microbial life extends far below the species level to the finest scales of genetic differences. Remarkably, extensive fine-scale diversity can coexist spatially. How is this diversity stable on long timescales, despite selective or ecological differences and other evolutionary processes? Most work has focused on stable coexistence or assumed ecological neutrality. We present an alternative: extensive diversity maintained by ecologically driven spatiotempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
100
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 82 publications
3
100
0
Order By: Relevance
“…Yet, it is difficult to imagine that the dynamics of enormously abundant species like Prochlorococcus are controlled primarily by neutral processes, which could be disrupted by even tiny differences between strains (9). In PNAS, Pearce et al (10) show analytically how alternative nicheless models can produce the same neutral abundance patterns from a dynamics that could hardly be more nonneutral: rapid spatiotemporal chaos generated by ecological interactions and random dispersal. Pearce et al (10) highlight that widely observed static patterns, believed to be hallmarks of neutrality, are too insensitive to distinguish pertinent scenarios, reinforcing the need for spatiotemporal data (11,12) in microbial ecology.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Yet, it is difficult to imagine that the dynamics of enormously abundant species like Prochlorococcus are controlled primarily by neutral processes, which could be disrupted by even tiny differences between strains (9). In PNAS, Pearce et al (10) show analytically how alternative nicheless models can produce the same neutral abundance patterns from a dynamics that could hardly be more nonneutral: rapid spatiotemporal chaos generated by ecological interactions and random dispersal. Pearce et al (10) highlight that widely observed static patterns, believed to be hallmarks of neutrality, are too insensitive to distinguish pertinent scenarios, reinforcing the need for spatiotemporal data (11,12) in microbial ecology.…”
mentioning
confidence: 99%
“…Do species go extinct en masse or become somehow stabilized dynamically? These are the central dynamical questions that Pearce et al (10) set out to answer because populations of closely related strains are, with only weak niche differences, poised to be May-unstable. Pearce et al (10) develop analytical techniques within the framework of dynamical mean-field theory that, like May's approach, leverage the simplicity that emerges in the large S limit.…”
mentioning
confidence: 99%
See 3 more Smart Citations